تأثير المعاملة بالبكتيريا وحمض الهيوميك وبعض الأحماض الأمينية في بعض المؤشرات الفسيولوجية والإنتاجية لصنف القطن124 (Gossypium hirsutum L.) - عبد العزيز محمد; يوسف عدلة وسيم; ابراهيم عاصم (Latakia University Journal -Biological Sciences Series, 2019)
تأثير المعاملة بالبكتيريا وحمض الهيوميك وبعض الأحماض الأمينية في بعض المؤشرات الفسيولوجية والإنتاجية لصنف القطن124 (Gossypium hirsutum L.) محمد عبد العزيز وسيم يوسف عدلة عاصم ابراهيم أجري البحث في محطة بحوث جب رملة التابعة لمركز بحوث الغاب – الهيئة العامة للبحوث العلمية الزراعية عام 2018، بهدف دراسة تأثير كل من (البكتيريا Bacillus B، وحمض الهيوميك H، والأحماض الأمينيةA ) وفق ثلاث مستويات (بدون 1، ورش المجموع الخضري 2، وسقاية النباتات 3) في بعض المؤشرات الفيزيولوجية والإنتاجية لصنف القطن 124 (Gossypium hersutum L.). طبق تصميم القطع المنشقة لمرتين بثلاثة مكررات، إذ احتل العامل الأول (البكتيريا B) القطع الرئيسية، بينما احتل العامل الثاني (حمض الهيوميك H) القطع المنشقة لمرة واحدة، واحتل العامل الثالث (الأحماض الأمينية A) القطع تحت المنشقة. أجري التحليل الإحصائي باستخدام برنامج Genestat.12 وحسب أقل فرق معنوي L.S.D. عند مستوى المعنوية 5%. شملت المؤشرات المدروسة عند بداية تفتح الجوزات: معدل نمو المحصول (غ/م2/أسبوع)، والكفاءة التمثيلية للمحصول (غ/م2/أسبوع)، ومحتوى الأوراق من عنصر الآزوت (%)، والفوسفور (%)، وغلة القطن المحبوب (كغ/ه). أظهرت النتائج تفوق التداخل بين سقاية النباتات بالبكتيريا وحمض الهيوميك مع رش المجموع الخضري بالأحماض الأمينية B3×H3×A2 معنوياً على الشاهد (بدون) B1×H1×A1 لدى مختلف المؤشرات المدروسة، وبلغت الزيادة عند معدل نمو المحصول 7.55(غ/م2/أسبوع)، والكفاءة التمثيلية للمحصول 1.58(غ/م2/أسبوع)، ومحتوى الأوراق من عنصر الآزوت 1.11(%)، والفوسفور 0.110(%)، وغلة القطن المحبوب 262.37(كغ/ه) بزيادة قدرها (8.23%) محققة للربح الاقتصادي مقارنة بالشاهد، وتعود أهمية تقدير غلة القطن المحبوب إلى أنه يمثل الجزء الاقتصادي الذي يزرع من أجله المحصول. The research was carried out at Jeb Ramlah Research Station – AlGhab Research Center - General Authority of Scientific Agricultural Research at 2018 growing season. The objective was to investigate the effect of (Bacillus Bacteria B, Humic acid H and Amino acids A) under three levels (Without 1, Vegetative spraying 2 and Plant irrigation 3) in some physiological and productivity traits of cotton var 124 (Gossypium herutum L.). Split Split Plot Design was used with three replications. The first factor (Bacteria B) occupied the main plots, while the second factor (Humic acid H) occupied the split plots, and the third factor (Amino acids A) occupied the sub-split plots. Statistical analysis was carried out using the Genestat.12 software and the least significant difference L.S.D. at 5% level was calculated. Studied traits included (at the beginning of Maturity stage): Crop growth rate (g/m2/week), Net assimilation rate (g/m2/week), Leaf content of nitrogen (%), Leaf content of phosphour (%) and Cotton yield (kg/ha). The results showed that the interaction between Plant irrigation by both Bacteria and Humic acid and Leaf spraying by Amino acids B3×H3×A2 was superiority significant comparing to the control B1×H1×A1, and increasing values was for Crop growth rate (7.55g/m2/week), Net assimilation rate (1.58g/m2/week), Leaf content of nitrogen (1.11%), Leaf content of phosphour (0.110%) and the cotton yield (262.37kg/h), with an increase of (8.23%) for the economic profit compared to the Control, and it is important to estimate the yield of cotton seed to represent the economic part for which the crop is grown.